1996
DOI: 10.1139/t96-030
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of a compacted silt

Abstract: This paper presents a qualitative and quantitative study of the microstructure of a compacted silt, carried out using a scanning electron microscope and mercury intrusion pore size distribution measurements. Samples have been statically compacted at three water contents: on the dry side of the standard Proctor optimum water content, at the optimum, and on the wet side. The wet sample has a matrix type structure, with a clayey fraction filling the voids and adhering to the silt-sized grains, whereas the other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
142
0
24

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(183 citation statements)
references
References 0 publications
17
142
0
24
Order By: Relevance
“…Lambe and Whitman, 1969;Mitchell et al, 1965) the engineering properties of compacted cohesive soils were related to the compaction state, which was explained by the dispersed microstructure of soil compacted on the wet side and flocculated microstructure of the soil compacted on the dry side of the Proctor compaction curve. Mercury intrusion porosimetry tests for cohesive soils confirmed that the microstructure on the dry side of optimum water content was composed of aggregates with a welldefined distinction between the 'intra-aggregate pore population' and the 'inter-aggregate pore population' full of air, because water was located only in the aggregates (Delage et al, 1996;Tarantino and De Col, 2008). For material compacted on the wet side of the Proctor optimum water content, the initial bimodal pore size distribution depends heavily on the state of saturation during compaction (Delage et al, 1996).…”
Section: Introductionmentioning
confidence: 87%
“…Lambe and Whitman, 1969;Mitchell et al, 1965) the engineering properties of compacted cohesive soils were related to the compaction state, which was explained by the dispersed microstructure of soil compacted on the wet side and flocculated microstructure of the soil compacted on the dry side of the Proctor compaction curve. Mercury intrusion porosimetry tests for cohesive soils confirmed that the microstructure on the dry side of optimum water content was composed of aggregates with a welldefined distinction between the 'intra-aggregate pore population' and the 'inter-aggregate pore population' full of air, because water was located only in the aggregates (Delage et al, 1996;Tarantino and De Col, 2008). For material compacted on the wet side of the Proctor optimum water content, the initial bimodal pore size distribution depends heavily on the state of saturation during compaction (Delage et al, 1996).…”
Section: Introductionmentioning
confidence: 87%
“…As the amount of fines increases, particles tend to group themselves into larger aggregates, whose size depends on the amount of water added. Soils (with an appreciable content of clay) compacted dry of optimum moisture content generally exhibit a fabric made up of aggregates of varying sizes and tend to have a bimodal pore size distribution, whereas soils compacted wet of optimum tend to display a dominant peak [8,12]. It has been widely accepted that the different behavioural features observed on soils compacted dry or wet of optimum moisture content are almost exclusively due to different structures set up during the process of compaction (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, few works on the microstructural behaviour on compaction are devoted to low-activity soils with clay content less than 25% (see, for example, [8]). These silty soils have a low tendency to form aggregates (especially at low water contents), which are difficult to detect, and thus, they present a microstructure usually characterised by a monomodal pore size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 reveals that the compaction water content affects the water content at quasi-saturated conditions. That can be explained with the increase of inter-aggregate pores with decreasing compaction water content [14,15]. The water in the comparatively large inter-aggregate pores drains as soon as the suction cells are lifted from the water basin and hence the measurable maximum water content at quasi-saturated conditions decreases.…”
Section: Resultsmentioning
confidence: 99%